1998
DOI: 10.1016/s0167-5877(98)00077-4
|View full text |Cite
|
Sign up to set email alerts
|

Proportional morbidity rates of enteropathogens among diarrheic dairy calves in central Spain

Abstract: Faecal samples from 218 diarrheic dairy calves in 65 dairy herds, selected by convenience, were screened for the presence of rotavirus, coronavirus, Cryptosporidium spp., F5+ Escherichia coli and Salmonella spp. Animals surveyed were from 1 to 30 days old. Cryptosporidium and rotavirus were the most commonly detected agents (52.3% and 42.7% of the samples positive, respectively). F5+ E. coli was detected in the faeces of 11.9% of the calves and bovine coronavirus was detected in the faeces of 7.3% of the calve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
6
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 10 publications
11
65
6
2
Order By: Relevance
“…Nevertheless, concurrent shedding of BoTV with one or more enteropathogens was more commonly observed in calves Յ6 months old than in older cattle Ͼ6 months old, which is in agreement with previous reports indicating an increase in the probability of detection of multiple pathogens in calves. 6,12,28 Others have reported that mixed infections by enteropathogens were more commonly observed in diarrheic calves than in healthy ones, 28 which suggests that the presence of more than one enteropathogen may be one of the determining factors for clinical disease. A combined effect between BoTV and other enteric pathogens such as rotaviruses and astroviruses has been re- ported under experimental conditions, where concurrent infection with BoTV and either of the 2 viruses induced a more severe clinical disease than did each virus alone.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, concurrent shedding of BoTV with one or more enteropathogens was more commonly observed in calves Յ6 months old than in older cattle Ͼ6 months old, which is in agreement with previous reports indicating an increase in the probability of detection of multiple pathogens in calves. 6,12,28 Others have reported that mixed infections by enteropathogens were more commonly observed in diarrheic calves than in healthy ones, 28 which suggests that the presence of more than one enteropathogen may be one of the determining factors for clinical disease. A combined effect between BoTV and other enteric pathogens such as rotaviruses and astroviruses has been re- ported under experimental conditions, where concurrent infection with BoTV and either of the 2 viruses induced a more severe clinical disease than did each virus alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous etiological agents may be implicated in this clinical symptom (De La Fuente et al 1998), group A rotavirus is one of the major causes of acute gastroenteritis in infants and in many animal species (Estes & Kapikian 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of E. coli F5 is lower than that found in diarrheic calves by [17] (11.9%) and by [13] (12.5%) in Spain, by [18] (3%) in southern Britain, by [15] (5.5%) in Switzerland and even in Belgium in 2005 (11.2%) (personal communication, ARSIA) but is in agreement with the prevalence of 2.6% found in Norway [14]. As for rotavirus and bovine coronavirus, the lower detection of E. coli F5 could be explained by an adequate transfer of the colostral immunity and a reduction of the infectious pressure related to the Locatim administration.…”
Section: Clinical Scoresmentioning
confidence: 64%
“…In the three farms, the lesser severity of diarrhoea is confirmed by the absence of significant dehydration resulting from a reduced fluid loss via faeces. Faecal Samples C. parvum was detected in 76% of faecal samples, which is higher than the prevalence of 32 to 55% observed in diarrheic calves in other studies [12][13][14][15]. However, a large proportion of samples were provided by diarrheic calves in which the shedding of C. parvum is showed to be significantly higher [14,16].…”
Section: Clinical Scoresmentioning
confidence: 72%